2006
DOI: 10.1038/nature04418
|View full text |Cite
|
Sign up to set email alerts
|

Stratified prokaryote network in the oxic–anoxic transition of a deep-sea halocline

Abstract: The chemical composition of the Bannock basin has been studied in some detail 1,2 . We recently showed that unusual microbial populations, including a new division of Archaea (MSBL1) 3 , inhabit the NaCl-rich hypersaline brine. High salinities tend to reduce biodiversity 4 , but when brines come into contact with fresher water the natural haloclines formed frequently contain gradients of other chemicals, including permutations of electron donors and acceptors, that may enhance microbial diversity, activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
234
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(242 citation statements)
references
References 30 publications
8
234
0
Order By: Relevance
“…Daffonchio et al 2006;Yakimov et al 2007a,b;La Cono et al 2011) and unicellular eukaryotes (e.g. Edgcomb et al 2009;Pachiadaki et al 2014) found in the seawater--brine interfaces and the brines of several of these systems.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Daffonchio et al 2006;Yakimov et al 2007a,b;La Cono et al 2011) and unicellular eukaryotes (e.g. Edgcomb et al 2009;Pachiadaki et al 2014) found in the seawater--brine interfaces and the brines of several of these systems.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, microbial life from all three domains has been shown to occur in such aquatic systems (e.g. van der Wielen et al 2005;Daffonchio et al 2006;Alexander et al 2009;Borin et al 2009;Yakimov et al 2007a). While new cell morphologies and ecophysiological traits have been assigned to some of these microorganisms, only recently a more specific picture of the metabolic activities of DHAB microorganisms has started to emerge, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first time that evidence for nitrogen fixation activity in a DHAB habitat is reported. In ammonium-rich environments such as the DHAB interfaces and brines (Daffonchio et al, 2006), dinitrogen fixation is expected to be inhibited (Madigan et al, 2008), but some organisms are capable of maintaining high N 2 fixation rates in the presence of a high level of ammonium. This was observed in isolates (Okoronkwo et al, 1989) and in natural populations from deep anoxic waters of the Baltic Sea (Farnelid et al, 2013).…”
Section: Metabolism Of Nitrogen Compoundsmentioning
confidence: 99%
“…Studies of Discovery, L'Atalante, Urania, Thetis and Bannock basins revealed that DHAB interfaces harbor abundant and diverse microbial communities that include numerous novel candidate divisions that are more productive than most pelagic marine systems (see, for example, Sass et al, 2001;Van Der Wielen et al, 2005;Yakimov et al, 2007;Edgcomb et al, 2009;Stock et al, 2012). Functional analyses of these communities based on PCR amplification of key functional genes as well as activity measurements revealed sulfur cycling and methanogenesis to be dominant prokaryotic metabolic processes supporting life in DHABs and contributing to observed elevated biomass in DHAB haloclines (Daffonchio et al, 2006;Yakimov et al, 2007;Borin et al, 2009). Recent advances in RNA isolation, amplification and high-throughput sequencing make it possible to acquire millions of sequences of transcribed genes from microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…They were formed 5000-40 000 years ago by dissolution of ancient subterranean salt deposits (Messinian evaporites) exposed to seawater by tectonic shifts and the downward flow of the dense brines into local abyssal depressions, followed by progressive development of anoxia in the brine lakes thereby formed (Fusi et al, 1996;Wallmann et al, 1997). Recent studies of DHALs revealed the existence of new microbial lineages flourishing within these harsh environments (Ferrer et al, 2005;van der Wielen et al, 2005;Daffonchio et al, 2006;Hallsworth et al, 2007;Yakimov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%